(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
Abstract The United Nations Convention against Corruption (art.7, para. 4) calls on each States Parties to establish, maintain and strengthen systems that promote transparency and prevent conflicts of interest. In their national legal systems, countries define the legal framework for the concept of conflict of interest and the range of officials for whom it is unacceptable to be in a situation of conflict of interest; determine the circle of persons of the official in relation to which the implementation of this official of his official duties is limited; empower the competent authorities to prevent and respond to officials in situations of conflict of interest, etc. Each state builds its own mechanism for the legal regulation of conflicts of interest. Determining the goals, objectives and principles of this mechanism, a person stands in the center of it. A person as an official who is being inspected, and a person as a representative of a supervisory body to prevent conflicts of interest in the activities of officials. With the rapid development of technologies (including artificial intelligence), more and more often, powers and solutions to various problems are transferred from a person to a machine in order to resolve them more efficiently. In this regard, the question arises whether artificial intelligence is able to significantly reduce the risks of a conflict of interest in state and municipal institutions. If artificial intelligence is authorized to implement this, then what will be the goals, objectives and principles of the mechanism for the legal regulation of conflicts of interest by artificial intelligence. Will these goals, objectives and principles contribute to the ordering of public relations, as well as to help meet the interests of the state and society.